Why is depression more common among women than among men? - Kühner, Christine (The lancet. Psychiatry, 2017)
Summary: Women are about twice as likely as are men to develop depression during their lifetime. This Series paper summarises evidence regarding the epidemiology on gender differences in prevalence, incidence, and course of depression, and factors possibly explaining the gender gap. Gender-related subtypes of depression are suggested to exist, of which the developmental subtype has the strongest potential to contribute to the gender gap. Limited evidence exists for risk factors to be specifically linked to depression. Future research could profit from a transdiagnostic perspective, permitting the differentiation of specific susceptibilities from those predicting general psychopathologies within and across the internalising and externalising spectra. An integration of the Research Domain Criteria framework will allow examination of gender differences in core psychological functions, within the context of developmental transitions and environmental settings. Monitoring of changing socioeconomic and cultural trends in factors contributing to the gender gap will be important, as well as the influence of these trends on changes in symptom expression across psychopathologies in men and women.
Available online 15 November 2016
Gesehen am 27.11.2018